(untitled) (Baghdad Science Journal, 2021)
Synthesis of 2-mercaptobenzothiazole (A1) is performed from the reaction of o-aminothiophenol and carbon disulfide CS2 in ethanol under basic condition. Compound (A1) is reacted with chloro acetyl chloride to give compound (A2). Hydrazide acid compound (A3) is obtained from the reaction of compound (A2) with hydrazine hydrate in ethanol under reflux in the presence of glacial acetic acid .The reaction of hydrazide acid compound (A3) with ethyl acetoacetate gives pyrazole compound (A4). The new hydrazone compound (A5) was prepared from the reaction of compound (A3) with benzaldehyde. Reaction of compound (A3) with thiourea dissolved in ethanol gave 2-amino thiazole compounds(A6) which was used the reaction with 4–N,N-dimethyl benzaldehyde to yield compound hydrazone (A7).While, the reaction of compound (A2) with urea in the presence of ethanol gave 2-amino oxazole compounds (A8) which was used in the reaction with 3-hydroxy – 4 -methoxy benzaldehyde to yield hydrazone (A9). The structures of the prepared compounds were established by spectral (1H-NMR,Elemental analysis (C.H.N- ),and FT-IR. In addition to systematic characterization of some active functional groups in these compounds, antibacterial activity (Esheriechia coli, Bacillus subtilis ) for some of the synthesized compounds were evaluated against two types of fugal (Candida albicans ) , the synthesized compounds.